Populism and its impact as a response to illegal immigration: Causes and implications - Al-Najjar, Mohammed Salem Saleh Mahdi (The International and Political Journal, 2023)
This study aims to shed light on the phenomenon of populism and its importance in terms of its transformation into an ideology, and to study its manifestations and spread in democratic and non-democratic societies. The study examines the roots and reasons for the return of populism to modern political life. Populism is a process of building political opinions and critical intellectual orientations among the general public. This phenomenon is often transformed into ideologically packed mass beliefs with the aim of gaining power. Populism appeared in the nineteenth century, and the actual interest in studying it emerged more in the twentieth century, following the rise of political currents and parties in Europe, especially the nationalist and extreme right-wing parties. It came as a means of expressing a political ideology that combines the policies of extremist Right and its rhetoric, through major events such as the US elections, which were the cause of the rise of Donald Trump and the rhetoric of the far-right populist, as well as the exit of Britain from the European Union in protest against the increasing flow of immigration coming from the Middle East and North Africa and increasing suspicions. European countries, and dissatisfaction with the economic policies of the European Union created a large gap within societies, and greatly affected the political, economic and social future of these countries.